Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.celrep.2015.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Monocyte-Derived Macrophages Control Commensal-Specific Th17 Responses

Abstract: Summary Generation of different CD4 T cell responses to commensal and pathogenic bacteria is crucial for maintaining healthy gut environment, but the associated cellular mechanisms are poorly understood. Dendritic cells (DCs) and macrophages (Mfs) integrate microbial signals and direct adaptive immunity. Although the role of DCs in initiating T cell responses is well appreciated, how Mfs contribute to the generation of CD4 T cell responses to intestinal microbes is unclear. Th17 cells are critical for mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 48 publications
2
94
2
1
Order By: Relevance
“…For example, monocyte-derived MHC2−hi APCs (28) contribute to the development of mucosal T H 17 cells, while Treg cells in the gut broadly require CD103+ cDCs (29). Recent work from our lab suggests that mucosal Treg development is also partially dependent on the CD11b+ fraction of CD103+ DCs in a monoclonal setting (30).…”
Section: Resultsmentioning
confidence: 99%
“…For example, monocyte-derived MHC2−hi APCs (28) contribute to the development of mucosal T H 17 cells, while Treg cells in the gut broadly require CD103+ cDCs (29). Recent work from our lab suggests that mucosal Treg development is also partially dependent on the CD11b+ fraction of CD103+ DCs in a monoclonal setting (30).…”
Section: Resultsmentioning
confidence: 99%
“…CX3CR1 + MNPs are involved in the induction of Th17 responses to intestinal bacteria (18) and are essential for the killing of Candida in the kidneys during systemic infection (19). Conversely, several studies have suggested a central role for IRF4-dependent CD11b + CD103 + DCs in intestinal Th17 cell differentiation, as well as Th17-induced bacterial and fungal clearance in the lung (12, 14).…”
mentioning
confidence: 99%
“…Intestinal bacteria could also contribute to the activation of IL-17A response in the intestinal mucosa of active CD patients and in subjects unresponsive to the GFD experimental models [27] . Therefore, theoretically, intestinal bacteria could also contribute to the activation of IL-17A response in the intestinal mucosa of active CD patients and in subjects unresponsive to the GFD [28] .…”
Section: Introductionmentioning
confidence: 99%